Improvements during long-term fasting in patients with long COVID – a case series and literature review - Grundler, Franziska; Mesnage, Robin; Cerrada, Alberto; Wilhelmi de Toledo, Françoise (Frontiers in Nutrition, 2023)
Background: Post-acute sequelae of a severe acute respiratory syndrome coronavirus 2 infection, also known as long COVID, comprises a variety of symptoms that impair the quality of life. This represents a growing public health burden, with millions of individuals worldwide affected. Case description: We present a case series of 14 COVID-19 patients with post-acute symptoms who underwent medically supervised long-term fasting (6 to 16 days) according to the peer-reviewed Buchinger Wilhelmi protocol. The EQ-5D-5L questionnaire and visual scales were used to evaluate the intensity of the symptoms, retrospectively during the acute phase, and prospectively before and after long-term fasting. Blood tests were also performed before and after fasting. Thirteen patients reported that fasting caused an enhancement in their perceived overall health. Only one patient had no improvement. Both frequent (fatigue, breathlessness, muscle and joint pains) and less frequent (cognitive impairment, smell and taste disorders) sequelae ameliorated. Body weight and other risk factors for cardiometabolic diseases like blood pressure, blood glucose, total cholesterol, low-density-lipoprotein cholesterol, and triglycerides were reduced. No severe side effects occurred. Discussion: This case series reports beneficial changes in self-perceived symptoms in patients with long COVID after long-term fasting. This highlights the potential of long-term fasting as an effective intervention for managing and treating long COVID.